Novel nano-structured material for indoor air quality control - Zhang, Li (2013)
Photo-catalytic technology is drawing more attentions in indoor air quality control.The appeal of this technology is the prospect of mineralization of the pollutants into harmless CO2 and H2O with the effective use of natural light. However, the most promising photo-catalyst TiO2 is only efficient under UV light irradiation (5% of solar light ), which will increase the cost significantly and may cause adverse health effect to human beings. Therefore, it is desirable to harness the huge visible-light portion (43% of solar light) with high efficiency for useful photocatalytic applications in order to establish an economical, clean and safe reaction system. [4th Award]